Biological monitoring of exposure to pesticide residues among Belgian florists. Issue 3 (15th March 2020) - Toumi, Khaoula; Joly, Laure; Vleminckx, Christiane; Schiffers, Bruno
Abstract: Many pesticides applied in cut flowers can be readily absorbed through the skin of florists during preparing bouquets and handling contaminated flowers. A study was conducted among volunteer Belgian florists in order to assess their total exposure by measuring concentrations of pesticides (parent compounds and metabolites) in their urines. A total of 42 urine samples (24-h urines) were collected from florists during their professional activities, on the three most important commercial periods. The concentrations of pesticide residues and metabolites in urine samples were analyzed with a multiresidue liquid chromatography tandem mass spectrometry method, after an ethyl acetate extraction. The results are compared with those of a control group of 42 subjects not occupationally exposed to pesticides, collected in the same periods. A total of 70 residues (56 pesticides and 14 metabolites) were identified, with an average of about eight pesticide residues and metabolites per florist's urine sample and an average total concentration per sample of 4.3 µg/g creatinine, ranging from 0.2 to 67 µg/g creatinine. Significantly higher urinary excretion of metabolites ( t -test) was found in florists than in control group. These results demonstrate that Belgian florists are exposed daily to pesticide residues with a potential effect on their health.